PENGARUH CUSTOMER EXPERIENCE DAN RELATIONSHIP QUALITY PADA REPURCHASE INTENTION PRODUK SKINCARE GARNIER MELALUI SERVICE QUALITY - Sunaryo Sunaryo; Indra Syafii; Maurin Dewi Prameswari (Insan Doktor Ekonomi Indonesia (IDEI), 2022)
This study aims to determine the effect of customer experience on repurchase intention through service quality and to determine the effect of relationship quality on repurchase intention through service quality. The sample of this study were users of Garnier skincare products in Medan Johor District, amounting to 150 respondents. The analysis technique used is path analysis. The results showed that customer experience had a positive and significant effect on repurchase intention mediated by service quality. Relationship quality has a positive and significant effect on repurchase intention mediated by service quality.Penelitian ini bertujuan untuk mengetahui pengaruh customer experience pada repurchase intention melalui service quality dan untuk mengetahui pengaruh relationship quality pada repurchase intention melalui service quality. Sampel dalam penelitian ini adalah pengguna produk skincare Garnier di Kecamatan Medan Johor yang berjumlah 150 responden. Teknik analisis yang digunakan adalah analisis jalur. Hasil penelitian menunjukkan bahwa customer experience berpengaruh positif dan signifikan pada repurchase intention yang dimediasi oleh service quality. Relationship quality berpengaruh postitif dan signifikan pada repurchase intention yang dimediasi oleh service quality.